Auschwitz. A Documentary Film on German Crimes at Oswiecim - Bykov, N.; Kutub-Zade, K.; Pavlov, A. (the Central Documentary Film Studio, 1945)
Duration: 00:21:00 This Soviet Army film of the liberation of Auschwitz Concentration Camp was awarded the Red Banner in 1945. It contains dramatic footage of the survivors and some of the atrocities perpetrated in this most notorious of camps, including captured German film of medical experiments performed on prisoners. Photography by cameramen of the First Ukrainian Front: N. Bykov, K. Kutub-Zade, A. Pavlov, A. Vorontzov.